Jacob Have I Loved - Paterson, Katherine (New York Harper Trophy, 1980)
feeling deprived all her life of schooling, friends, mother, and even her name by her twin sister, louise finally begins to find her identity
American Corner
Winner Of The John Newbery Medal
11
Keywords: English Fiction; English Stories